5 - Crise alimentaire et problématique du développement économique et social en Afrique au Sud du Sahara - François Bicaba (Africa Development, 1987)
The focus oi the study is on the prevailing food crisis in Africa and the author argues that it cannot be solved by merely applying a food import policy however cheap this import might be, or'by hastily and incoherently implementing policies of food self sufficiency. The only solution lies instead in a re- orientation of agricultural development policies and in overall changes of development strategies. A number of internal and external factors are at the root of this crisis. Over and beyond drought and natural disasters there seems to be three major internal causes of the crisis. Namely: A wrong conception of agricultural development and of its role in the national economy which have led to meaningless separation of food and export crops which should have been an integrated undertaking. Industrial policies which are propitious to the socio-economic, physical and international environment but which in the end do not get implemented because of mismanagement in the widest sense of the word. Lack of a conceptual approach whereby export crops are seen first and foremost as raw materials for industry before being considered as export crops. As for the external factors there are two outstanding elements: The colonial legacy and the world economic crisis. To start with, African states have hardly any influence on the way the world economy is run. But with the crisis, their rather low participation rate in international trade is getting even lower. In response to the crisis, a geographical and a technological re-organization of industry are developing. This re-adjustment has meant a lower demand for African agricultural products on the world market. In view of the present evolution of the world economy, the export of primary products as a mode of accumulation of capital is no longer viable. Indeed a new international economic order being implemented by MNCs is rearing its head and stealthily taking the lead. This phenomenon explains why for instance the palm oil industry and that of its by-products are being moved from Africa to Asia (Malaysia) and to the U.S.A. In view of these different parameters on which the world economic trend depends in the long-run and of the final objective of the food issue which is food security, it is more than ever necessary to re-direct strategies for economic development in Africa. The new orientation should be based on agricultural and rural development, the actors of which cannot be multinational corporations - but rather the small peasants. However, in isolation, African economies are fragile; there is therefore a decisive need to promote regional economic cooperation. In addition to acting as pressure groups in international relations, these regional groupings can ensure regional food self-sufficiency. National food sufficiency requires an organized market which will make a selected number of priority food items available in accordance with the framework of a production plan. It will then be up to every State to distribute food commodities to the poorest populations whose plight might be due to their geographical location or to unequal distribution of national income. Such a strategy has three advantages: - It can create rural employment and curb migration to the cities; - promotes the expansion of the locally manufactured goods market and, - eventually improves the margin of manoeuvre of African States in their external dealings and gradually strengthens their economic sovereignty in a world characterized by economic guerrilla warf